2018
DOI: 10.4077/cjp.2018.bag551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroid Dysfunction on Reproductive Hormones in Female Rats

Abstract: Thyroid hormones (THs) play a critical role in the development of ovarian cells. Although the effects of THs on female reproduction are of great interest, the mechanism remains unclear. We investigated the effects of TH dysregulation on reproductive hormones in rats. Propylthiouracil (PTU) and L-thyroxine were administered to rats to induce hypo- and hyperthyroidism, respectively, and the reproductive hormone profiles were analyzed by radioimmunoassay (RIA). Ovarian histology was evaluated with hematoxylin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…These results were in agreement with many studies, showed that serum prolactin was significantly (P<0.05) higher in infertile group with thyroid dysfunction compared with control [9,20,34].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results were in agreement with many studies, showed that serum prolactin was significantly (P<0.05) higher in infertile group with thyroid dysfunction compared with control [9,20,34].…”
Section: Discussionsupporting
confidence: 93%
“…These data in agreement with Liu et al, who found that the serum levels of gonadotropin releasing hormone (GnRH) and follicle stimulating hormone (FSH) in both hypo-and hyperthyroidism rat models were significantly decreased on the luteal phase, although there were no significant changes at earlier time points. There were no significant differences in luteinizing hormone (LH) or progesterone levels between the treatment and the control groups [9].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In recent times, multiple studies have been conducted to observe the effect of thyroid dysfunction on the reproductive system [ 18 ]. This study was designed to observe the effect of experimentally induced hyperthyroid state on ovarian parameters and hypophyseal-gonadal axis, in adult Wistar albino rats.…”
Section: Discussionmentioning
confidence: 99%